Advances in pathological understanding of high-grade B cell lymphomas. Issue 8 (3rd August 2018) - Li, Shaoying; Lin, Pei; Medeiros, L. Jeffrey
ABSTRACT: Introduction : The designation high-grade B-cell lymphoma (HGBL) has been incorporated into the 2016 Revision of the WHO classification of lymphoid neoplasms and includes two types: (1) HGBL, not otherwise specified; and (2) HGBL with MYC and BCL2 and/or BCL6 rearrangements, also known as double or triple hit lymphoma (DHL/THL). These categories of lymphomas represent 1–2% of non-Hodgkin lymphomas and a considerable portion of DLBCL patients who are primary refractory to R-CHOP therapy. It corresponds to the designation 'B-cell lymphoma, unclassifiable, with features intermediate between DLBCL and Burkitt lymphoma' in the 2008 WHO classification. Areas covered : This paper provides an update of HGBL, focusing on their pathologic features, prognosis, and diagnostic workup. It highlights advances in our understanding of DHL/THL. Expert commentary : The diagnosis relies on FISH testing and the major controversial question is when to perform it to diagnose virtually all DHL/THL cases, but also being cost effective. Currently there is no consensus. Considering the high refractory rate of these patients to standard R-CHOP induction, the authors recommend FISH testing in all newly diagnosed large B-cell lymphoma by using our stepwise test strategy. With the progress of molecular genetics, the prognosis will be further stratified and HGBL-NOS maybe further evolve too.